Analisis Yuridis Terhadap Perjanjian Kerja Waktu Tertentu (PKWT) “UD. Permata Furni” - Ulfi Nihaya; Achmad Busro (Notarius, 2022)
AbstractProtection for workers is very necessary in order to provide basic rights for every worker, to guarantee equal opportunities and grants in general, in order to realize the welfare of workers. Therefore, work agreements must be in accordance with the law so that their use can provide fair rights for workers. The purpose of this paper is to find out and analyze work agreements, especially work agreements for a certain time (PKWT) between workers and “UD. Furni Gems". The preparation of this writing was carried out using a normative juridical research approach. Based on the results of the study, it was concluded that, l) Employment agreements, especially work agreements for a certain time (PKWT) must be in accordance with the provisions of Law Number 13 of 2003 concerning Manpower. 2) UD. PERMATA FURNI in Article 1 is inconsistent with and contrary to Article 58 of Law Number 13 of 2003 concerning Manpower, and Article 4 of the work agreement is not appropriate and contradicts Article 54 of Law Number 13 of 2003 concerning Manpower regarding the omission of wages and the method of payment which is a mandatory part of the employment agreement.Keywords: salary; time period; certain time work agreement (pkwt)AbstrakProteksi bagi buruh sangat diperlukan guna memberikan hak dasar setiap buruh, untuk menjamin peluang serta pemberian sama pada umumnya, demi mewujudkan kesejahteraan pekerja. Oleh karena itu, perjanjian kerja harus sesui dengan undang-undang agar pemanfaatannya dapat memberikan hak yang adil bagi pekerja. Tujuan dari penulisan ini guna mengetahui dan menganalisa perjanjian kerja khususnya perjanjian kerja waktu tertentu (PKWT)  antara pekerja dengan “UD. Permata Furni”. Penyusunan penulisan ini dilakukan menggunakan metode pendekatan penelitian yuridis normatif. Berdasarkan hasil penelitian disimpulkan bahwa, l) Perjanjian kerja khususnya perjanjian kerja waktu tertentu (PKWT) harus sesuai dengan ketentuan Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan. 2) Perjanjian Kerja Waktu Tertentu (PKWT) UD. PERMATA FURNI dalam Pasal 1 tidak sesuai dan bertentangan dengan Pasal 58 Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan, dan Pasal 4 perjanjian kerja tersebut tidak sesuai dan bertentangan dengan Pasal 54 Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan terkait tidak dicantumkannya besaran upah dan cara pembayarannya yang merupakan bagian wajib dalam perikatan kerja.Kata kunci : upah; jangka waktu; perjanjian kerja waktu tertentu (pkwt)